(untitled) (Research, Society and Development, 2021)
This article presents the results of a research, which aims to investigate how the experience of educational practice took place at the beginning of the COVID-19 pandemic, its implementation and the impacts on teacher education and student learning regarding the use of networks learning programs in state public schools in the municipality of Alto Longá – PI. For data collection, a qualitative approach was used and the instrument was the online questionnaire. Based on the legal documents that govern Brazilian education and theoretical contributions, we started from a reflection on a real situation experienced in this pandemic time, where we were able to share the concerns, experiences and methods developed for the planning, implementation and execution of non-presential classes. The results showed the importance and challenges of teaching work in this scenario, which demonstrates a precariousness in the implementation of this alternative, with regard to the deficits in care and use of digital technologies in the education network, which have generated an undesired situation of improvisation. and social exclusion.